1991
DOI: 10.4197/sci.3-1.2
|View full text |Cite
|
Sign up to set email alerts
|

Growth Phases of Some Antibiotics Producing Streptomyces and their Identification

Abstract: The growth phases of five cultures of antibiotic producing Streptomyces isolated from western region, Saudi Arabia were studied special al reference to their potentiality to excrete antibiotics. It was found that these organisms grew exponentially during the first 4 to 7 days of incubation. The highest specific growth "rate was observed in the case of Streptomyces MY18 being 0.48 day-l (1.44 days doubling time). This isolate also showed the highest inhibition zone against Staph. aureus as compared with the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…It has been reported that two phases are observed during the propagation of antibiotic producers. The first phase (trophophase) is characterized by rapid growth (biomass production) and the second phase (idiophase) is characterized by a slow growth and maximal productivity of antibiotics [30]. For isolate R3 and Y8, a similar result was recorded where maximum antibiotic activity could be seen on eighth and tenth day and then it was almost stable.…”
Section: Effect Of Incubation Period On Bioactive Metabolite Productionsupporting
confidence: 69%
“…It has been reported that two phases are observed during the propagation of antibiotic producers. The first phase (trophophase) is characterized by rapid growth (biomass production) and the second phase (idiophase) is characterized by a slow growth and maximal productivity of antibiotics [30]. For isolate R3 and Y8, a similar result was recorded where maximum antibiotic activity could be seen on eighth and tenth day and then it was almost stable.…”
Section: Effect Of Incubation Period On Bioactive Metabolite Productionsupporting
confidence: 69%
“…These unfavorable conditions are believed to adversely affect the expression of microbial secondary metabolites (Griffin, 1995). According to Sejiny (1991), during the propagation of antibiotics producers, two phases were observed which were trophophase and idiophase. Trophophase is characterized by rapid growth of microbial cells producing biomass and during the idiophase, slow microbial growth was observed and maximal antibiotic production was obtained.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of media constituents and fermentation conditions on antibiotic production were determined by varying the one factor at a time and base fermentation conditions were kept constant, i.e ., pH 6.5, temperature 30 °C, carbon source 1% w/v, nitrogen source 0.5% w/v, NaCl 0.50% w/v, inoculum 5% v/w, agar 1.5% w/v, and incubation period of 7 days. After completing each set of fermentation, the yield of antimicrobial extract was measured in mg/kg of fermented agar 53 , 61 , 62 , 73 , 74 .…”
Section: Methodsmentioning
confidence: 99%